Enhancing EFL Learners’ Motivation through Songs - Reza Anggriyashati Adara (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
ABSTRACTImproving learners’ motivation is an essential task for teachers because it can maintain learners’ interest in learning. This is why teachers employ numerous motivational strategies in order to enhance learners’ motivation. One of the strategies that can enhance learners’ motivation is using songs in English classrooms. The present study aims to analyse the effects of using songs in EFL classrooms on EFL learners’ motivation. The study used an experimental method by dividing the respondents into two groups: the experimental and control classes. While the control class was taught English conventionally, the experimental class lessons were integrated with English songs. Furthermore, a set of questionnaires and semi-structured interviews were administered in order to obtain the data. The findings suggest that songs seem to have positive effects on EFL learners’ motivation. Besides, using songs in EFL classrooms helps learners absorb new vocabulary and make English lessons more engaging. Thus, English teachers need to consider using English songs in their classrooms to improve learners’ motivation. Nevertheless, songs need to be suited to the learners’ level of English, age, and characteristics of the lessons.ABSTRAKMeningkatkan motivasi siswa adalah tugas penting bagi guru karena hal itu bisa meningkatkan minat siswa dalam belajar. Hal itu yang membuat guru menerapkan berbagai strategi motivasional demi meningkatkan motivasi siswa. Salah satu strategi yang dapat digunakan untuk meningkatkan motivasi siswa adalah menggunakan lagu-lagu di kelas-kelas bahasa Inggris. Penelitian ini bertujuan untuk menganalisis efek-efek lagu dalam peningkatan motivasi di kelas-kelas bahasa Inggris. Penelitian ini menggunakan metode eksperimental dengan membagi responden ke dalam dua grup: eksperimental dan kontrol. Kelas kontrol belajar bahasa Inggris secara konvensional sedangkan kelas eksperimental belajar bahasa Inggris dengan pelajaran yang diintegrasikan dengan lagu. Selain itu penelitian ini menggunakan kuesioner dan wawancara semi terstruktur untuk mendapatkan hasilnya. Penelitian ini mengindikasikan lagu dapat memotivasi siswa untuk belajar bahasa Inggris dan mendapatkan kosakata baru. Oleh karena itu, guru harus mempertimbangkan penggunaan lagu dalam kelas-kelas bahasa Inggris untuk meningkatkan motivasi siswa. Namun, penggunaan lagu perlu disesuaikan dengan level kemampuan bahasa Inggris, usia dan karakteristik pelajaran.